Overcoming barriers in care for the dying: Theoretical analysis of an innovative program model. (8th August 2016) - Wallace, Cara L.
ABSTRACT: This article explores barriers to end-of-life (EOL) care (including development of a death denying culture, ongoing perceptions about EOL care, poor communication, delayed access, and benefit restrictions) through the theoretical lens of symbolic interactionism (SI), and applies general systems theory (GST) to a promising practice model appropriate for addressing these barriers. The Compassionate Care program is a practice model designed to bridge gaps in care for the dying and is one example of a program offering concurrent care, a recent focus of evaluation though the Affordable Care Act. Concurrent care involves offering curative care alongside palliative or hospice care. Additionally, the program offers comprehensive case management and online resources to enrollees in a national health plan (Spettell et al., 2009).SI and GST are compatible and interrelated theories that provide a relevant picture of barriers to end-of-life care and a practice model that might evoke change among multiple levels of systems. These theories promote insight into current challenges in EOL care, as well as point to areas of needed research and interventions to address them. The article concludes with implications for policy and practice, and discusses the important role of social work in impacting change within EOL care.